The longitudinal effect of antipsychotic burden on psychosocial functioning in first-episode psychosis patients: the role of verbal memory. Issue 12 (24th September 2021) - Ballesteros, Alejandro; Sánchez Torres, Ana M.; López-Ilundáin, Jose; Mezquida, Gisela; Lobo, Antonio; González-Pinto, Ana; Pina-Camacho, Laura; Corripio, Iluminada; Vieta, Eduard; de la Serna, Elena; Mané, Anna; Bioque, Miquel; et al.
Abstract: Background: Previous literature supports antipsychotics' (AP) efficacy in acute first-episode psychosis (FEP) in terms of symptomatology and functioning but also a cognitive detrimental effect. However, regarding functional recovery in stabilised patients, these effects are not clear. Therefore, the main aim of this study is to investigate dopaminergic/anticholinergic burden of (AP) on psychosocial functioning in FEP. We also examined whether cognitive impairment may mediate these effects on functioning. Methods: A total of 157 FEP participants were assessed at study entry, and at 2 months and 2 years after remission of the acute episode. The primary outcomes were social functioning as measured by the functioning assessment short test (FAST). Cognitive domains were assessed as potential mediators. Dopaminergic and anticholinergic AP burden on 2-year psychosocial functioning [measured with chlorpromazine (CPZ) and drug burden index] were independent variables. Secondary outcomes were clinical and socio-demographic variables. Results: Mediation analysis found a statistical but not meaningful contribution of dopaminergic receptor blockade burden to worse functioning mediated by cognition (for every 600 CPZ equivalent points, 2-year FAST score increased 1.38 points). Regarding verbal memory and attention, there was an indirect effect of CPZ burden on FAST ( b = 0.0045, 95% CI 0.0011–0.0091) and ( b = 0.0026, 95% CI 0.0001–0.0006) respectively. However, only verbal memory post hoc analyses showed a significant indirect effect ( b = 0.009, 95% CI 0.033–0.0151) adding premorbid IQ as covariate. We did not find significant results for anticholinergic burden. Conclusion: CPZ dose effect over functioning is mediated by verbal memory but this association appears barely relevant.